Systematic consideration of floral microcharacters of the South American genus Chrysolaena (Vernonieae, Asteraceae). Issue 2 (3rd March 2016) - Via do pico, Gisela M.; Vega, Alvaro J.; Dematteis, Massimiliano
Abstract : Floral microcharacters of the genus Chrysolaena H. Rob. (Vernonieae, Asteraceae) were analysed in detail for the first time in order to evaluate the taxonomic position of conflictive species in the group. The results were also compared with studies carried out in species of related genera. In addition to distinctive microcharacters previously studied in some species of the genus, other characters such as trichome types of the corolla, style, anthers and cypselae have been analysed for the first time. The presence of glandular apical appendage and cypselae are common characteristics among species Chrysolaena . In addition to these, this study shows that presence of glands on the style and corollas is another consistent characteristic in the genus. However, the absence of basal stylar node would not be a diagnostic character since this varies widely among species. The results indicate that most of the microcharacters of Chrysolaena analysed are quite consistent in the genus, but they are no more consistent than the pollen morphology (type 'C') and chromosome base number ( x = 10). Until now, these last two features would be most useful for separating Chrysolaena from the related genera Lessingianthus and Lepidaploa . At species level, the results show that related species can be distinguished by the different combinations of floral microcharacters. The value of microcharacters could be increased if they are combined with other morphological, cytological, and palynological data.